Predicting bad utility consumers in Malaysia - Hoe A.C.K.; Dhillon J.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Data mining; CRISP-DM; Cross industry; Cumulative amount; Data preparation; Solution model; Utility bills; Utility companies; utility consumers; Sales